ASSOCIATION OF WT1 AND INDUCTION OF APOPTOSIS IN ENDOMETRIOTIC CELL LINES TREATED WITH MIS - Karipcin, S. F.; Fangxian, L.; Borahay, M.; Tekedereli, I.; Gurates, B.; Kilic, S. G. (Elsevier Science Inc, 2010)
[Abstract Not Available]
Annual Meeting of the American-Society-for-Reproductive-Medicine (ASRM 2010) -- OCT 23-27, 2010 -- Denver, CO